Growing a tumor stroma: a role for granulin and the bone marrow - Bateman, Andrew (American Society for Clinical Investigation, 2011)
The tumor stroma is critical in cancer progression; understanding its formation is therefore important biologically and therapeutically. In this issue of the JCI, Elkabets et al. report on the generation of data in mice that lead them to propose that certain tumors can stimulate the growth of a second otherwise quiescent or indolent tumor in the same animal by stimulating stromal formation. Granulin-expressing Sca(+)Kit(–) hematopoietic progenitor cells in the bone marrow of the tumor host were required to mediate this effect. These data shed new light on the importance of the bone marrow in tumor growth and the role of granulin in carcinogenesis.